Efficient antiglioblastoma therapy in mice through doxorubicin-loaded nanomicelles modified using a novel brain-targeted RVG-15 peptide. (21st October 2021) - Han, Mingfeng; Xing, Haoyue; Chen, Liqing; Cui, Minhu; Zhang, Yingying; Qi, Lingling; Jin, Mingji; Yang, Yang; Gao, Chunsheng; Gao, Zhonggao; Xing, Xuezhong; Huang, Wei
Abstract: Glioblastoma (GBM) is an aggressive malignancy and therapeutic options are limited due to the presence of the blood–brain barrier (BBB). RVG-29, a 29-amino-acid polypeptide derived from the rabies virus glycoprotein (RVG), has excellent brain-targeted capacity across the BBB. We reduced the size of this peptide to get a15-amino-acid polypeptide (RVG-15), while retaining its brain-targeted capacity across the BBB. First, we synthesized a novel nanocarrier RVG-15-PEG2000 -DSPE. Next, DOX-loaded polymeric micelles (DOX RVG-15-PMs) were prepared in an electrostatic interaction-dependent manner. Finally, we evaluated its antitumor benefits in vitro at the cellular level and in vivo using an in situ tumour-bearing mouse model. MALDI-TOF-MS and FTIR spectra confirmed the successful synthesis of the novel nanocarrier. The prepared DOX RVG-15-PMs displayed even size distribution, a high entrapment efficiency and satisfactory in vitro release behaviour. In vitro blank RVG-15-PMs were excellent, safe and highly biocompatible as drug delivery carriers. DOX-loaded micelles were easily taken up by C6 cells and could effectively inhibit cancer development and metastasis. In vivo, DOX RVG-15-PMs delayed weight loss, prevented cancer cell metastasis and accelerated cancer cell apoptosis in tumour-bearing mice. Our novel brain-targeted nanocarrier is highly feasible, while DOX RVG-15-PMs exert significant antiglioma effects, both in vitro and in vivo .